Explorando as possibilidades estéticas e imersivas dos fenômenos em The Backrooms e espaços liminares na arte e em jogos eletrônicos - Sabóia, Gabriel Henrique Rodrigues (Universidade Federal de São Carlos, 2026)
The Backrooms legend emerges on the internet in 2019 and becomes a cultural phenomenon by articulating human experiences within transitional spaces. Concepts such as liminality, the intermediate phase of a ritual (Van Gennep, 1919; Turner, 1974), the uncanny (Freud, 2019), and the non-place (Augé, 1994) guide the reflection on the aesthetics and narrative of the legend constructed by online communities. Its visual impact is analyzed based on key authors in anthropology, netnography, culture, audiovisual narrative, and art. As a result, a set of audiovisual works and analytical reflections contributes to defining and deepening the aesthetics of liminality, seeking to position itself as both a methodological and sensitive reference for future investigations and creations concerning emerging narratives and new aesthetics in contemporary audiovisual media.
Exploring the aesthetic and immersive possibilities of The Backrooms phenomena and liminal spaces in art and video games
Keywords: Liminaridade; Backrooms; Creepypasta; Audiovisual; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::COMUNICACAO VISUAL; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO; 4. Educação de Qualidade